Literasi Kewirausahaan Dan Munculnya Wirausaha Mahasiswa: Apakah Ada Hubungan? - Rizky Dwi Putri; Rizza Megasari; Dian Rachmawati; Ro’ufah Inayati (Unit Publikasi Ilmiah, P3M, Politeknik Negeri Bali, 2021)
This article aims to identify how entrepreneurship literacy could trigger the emergence of potential entrepreneurs from students. This paper presented a case study of the implementation of learning innovations for entrepreneurship courses using the project-based learning (PjBL) models. The implementation of PjBL on entrepreneurship subjects aims to instill an entrepreneurial spirit in students and motivate them to become entrepreneurs. This phenomenology research uses primary data through observation and interview with respondents that attended entrepreneur courses. The result of the business plan arranged by the student was analyzed and the internalization measurement of entrepreneurial spirit was conducted through student activities in class. This study has identified the criteria such as discipline, creativity, responsibility, leadership, decision-making, learning motivation, and communication skill through classes. Based on the in-depth interviews with eight students of entrepreneurship courses, the PjBL could stimulate students to improve entrepreneurial character, mindset, and skill to support participation and performance in a range of entrepreneurial activities. The entrepreneurial spirit showed a significant difference between before and after class which can see not only in the business plan and student’s presentation skills, also in their dream to continue the business there has been started. Furthermore, this study alternated formulation for entrepreneur courses in higher education.